Penerapan Supervisi Akademik Untuk Mengubah Sikap Konservatif Guru Di SMP Negeri 1 Teupah Tengah Kabupaten Simeulue Tahun 2022 - Ali, Safri (Journal of Technology and Literacy in Education, 2022)
The world of education requires teachers to improve their professionalism. For this reason, teachers must change their conservative attitude / maintain the usual way of carrying out their duties, especially in carrying out learning. The formulation of the problem in this study is how to change the conservative attitude of teachers through academic supervision at Teupah Tengah Public Middle School 1, Simeulue Regency in 2022. The research objective is to change the conservative attitude of teachers to become futuristic progressive teachers through academic supervision at Teupah Tengah 1 Public Middle School, Simeulue Regency in 2022 This research was conducted at SMP Negeri 1 Teupah Tengah, Simeulue Regency in odd semesters for three months starting from July to September in 2022. The research subjects were 8 teachers at SMP Negeri 1 Teupah Tengah Simeulue Regency. This research is a School Action Research (PTS) which is in the form of a cycle. Each cycle consists of the planning stage, the action implementation stage, the observation stage and the reflection stage which is carried out in two cycles. The data collection technique in this study was obtained from the results of observing the evaluation of teacher performance in learning. The data analysis technique used in this research is descriptive qualitative using average calculations and percentages. The results showed that in cycle I the total score of the observations obtained was 971 with an average percentage of 71.4% with good criteria. There are 4 teachers who get sufficient criteria and 4 teachers get good criteria. In cycle II the total score of the observations obtained was 1182 with an average percentage of 86.9% and obtained very good criteria. The total score increase from cycle I was 211 and the average percentage increase was 15.5%. As many as 5 teachers got good criteria and 3 teachers got very good criteria. So it can be concluded that through the implementation of academic supervision it can change the conservative attitude of teachers at SMP Negeri 1 Teupah Tengah Simeulue Regency in 2022.